An Improved Ventilation System for Settling Stage of a Wastewater Treatment Plant: A Computational Simulation Analysis - Polanco-Guzman, I; Vasco-Calle, D (Taylor and Francis Ltd., 2023)
The present study examines the development of a push-pull ventilation system with localized extraction located for use in wastewater treatment. The proposed approach aims to minimize the concentration of H2S in the settling stage of a wastewater treatment plant located in Santiago de Chile. Computational fluid dynamic simulations were implemented, and these were contrasted with actual measurements of H2S emission to assess and to improve the existing forced crossed ventilation system in place. Along with the measurement of H2S emissions, other important operating parameters of the existing ventilation system, including air velocity and NH3 concentration were measured. The measurements at different positions of the settling stage of the wastewater treatment process showed H2S concentrations as high as 21 mg/m3 at the center over the water surface when utilizing the existing crossed ventilation system. In general, the measured H2S concentrations agree with those predicted by computational simulations, with discrepancies between 8.1% and 28.4%. An assessment of the improved ventilation system with localized extraction systems (push-pull) was carried out to determine the level of effectiveness of decreasing the concentration of H2S in the settling plant. According to the obtained results, the concentration of H2S in the corridors of the plant does not surpass 7.5 ppm, which meets the required Chilean regulation. © 2020 Informa UK Limited, trading as Taylor & Francis Group.